2021
DOI: 10.3389/fmicb.2021.709571
|View full text |Cite
|
Sign up to set email alerts
|

A Type I Restriction Modification System Influences Genomic Evolution Driven by Horizontal Gene Transfer in Paenibacillus polymyxa

Abstract: Considered a “Generally Recognized As Safe” (GRAS) bacterium, the plant growth–promoting rhizobacterium Paenibacillus polymyxa has been widely applied in agriculture and animal husbandry. It also produces valuable compounds that are used in medicine and industry. Our previous work showed the presence of restriction modification (RM) system in P. polymyxa ATCC 842. Here, we further analyzed its genome and methylome by using SMRT sequencing, which revealed the presence of a larger number of genes, as well as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In contrast, the type IV R–M system lacks methyltransferases and instead specifically recognizes methylated DNA. This mechanism may act against phages attempting to evade defense systems through modified genomes [ 51 ]. The finding of Type IV requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the type IV R–M system lacks methyltransferases and instead specifically recognizes methylated DNA. This mechanism may act against phages attempting to evade defense systems through modified genomes [ 51 ]. The finding of Type IV requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that clusters are enriched in different types of R-M systems and it is widely recognised that similarity and compatibility of R-M systems between strains promote HGT and vice versa 48 . Indeed, studies show that type I and type III-like R-M systems can act as genetic barriers in Paenibacillus polymyxa 49 , Enterococcus faecium 50 , and Staphylococcus aureus 51 , 52 . We found that Type IV R-M systems are exclusively enriched in Cluster 1.…”
Section: Discussionmentioning
confidence: 99%
“…Insertion sequences (ISs) are short DNA sequences that function as simple transposable elements. They are often smaller than other transposable elements and encode only proteins involved in transposition [ 153 ]. In the genomes of isolates BB10.1 and BP20.15, copies of the insertion sequences ISBsu1 and ISBpu1 were found, while BB10.1 also had a copy of ISBspe1.…”
Section: Discussionmentioning
confidence: 99%